A review on the causative agents, risk factors and management of ventilator associated Pneumonia: from South Asian perspective - Naboni, Nahian Sanjida (Brac University, 2022)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2021.